An Analysis of Artificial and Natural Graphite in Lithium Ion Pouch Cells Using Ultra-High Precision Coulometry, Isothermal Microcalorimetry, Gas Evolution, Long Term Cycling and Pressure Measurements. Issue 14 (1st January 2017) - Glazier, S. L.; Li, Jing; Louli, A. J.; Allen, J. P.; Dahn, J. R.
Abstract : Natural graphite (NG) negative electrode materials can perform poorly compared to synthetic, or artificial, graphite (AG) negative electrodes in certain lithium ion cells. LiNi0.5 Mn0.3 Co0.2 O2 (NMC532)/(AG or NG) pouch cells were tested with various loadings of an electrolyte additive blend to study the effect of the graphite type as well as the formed solid electrolyte interphase (SEI). Cells underwent testing using ultra-high precision coulometry, isothermal microcalorimetry, in-situ pressure measurements, long term cycling and in-situ gas measurements. In short term experiments NMC532/AG and NMC532/NG cells showed similar coulombic efficiencies, parasitic heat flows, and gas production with large electrolyte additive loadings, but NG cells showed worse capacity retention in long-term tests. With low additive loadings NMC532/NG cells showed lower coulombic efficiency, higher capacity fade, more parasitic heat flow, and more gas production. In-situ cell stack pressure measurements showed that NMC532/NG cells irreversibly expanded during cycling while NMC532/AG cells did not. Although these results lead one to propose a simple model for the poor performance of NMC532/NG cells, NMC622/NG and NMC622/AG cells showed very different behavior in long term tests suggesting that positive/negative interactions play a strong role in governing the behavior of graphites in Li-ion cells.